The hospital anxiety and depression scale, in patients with multiple sclerosis - Pais-Ribeiro JL (Neuropsychiatric Disease and Treatment, 2018)
José Luís Pais-Ribeiro,1,2 Ana Martins da Silva,3,4 Estela Vilhena,5 Inês Moreira,3 Ernestina Santos,3,4 Denisa Mendonça6 1William James Center for Research, ISPA – University Institute, Lisboa, Portugal; 2Faculty of Psychology and Education Sciences of the University of Porto (FPCEUP), Porto, Portugal; 3Neurology Department, Centro Hospitalar do Porto-Hospital de Santo António (CHP-HSA), Porto, Portugal; 4Unit for Multidisciplinary Research in Biomedicine (UMIB), Abel Salazar Institute of Biomedical Sciences-University of Porto (ICBAS-UP), Porto, Portugal; 52Ai-Polytechnic Institute of Cávado and Ave, Barcelos, Portugal; 6Institute of Public Health of the University of Porto (ISPUP), Porto, Portugal Purpose: Multiple sclerosis (MS) is a long-lasting disabling disease with psychological implications. Hospital Anxiety and Depression Scale (HADS) is a questionnaire developed to screen anxiety and depression among patients in hospital settings. The objective of this report was to study the metric properties of the Portuguese version of HADS regarding MS. Materials and methods: This was a cross-sectional study. Three hundred and eighty individuals with a diagnosis of MS, according to the revised McDonald criteria, were recruited from an outpatient Neuroimmunology Clinic of the city of Porto. Participants had a mean age of 40.04 years (SD =10.86), 63.9% of them were female. HADS consists of two subscales – anxiety and depression – scored separately, with seven items each. Results: The results of our study show the appropriateness of HADS for the identification of mood changes in people with MS and show good metric properties. Conclusion: It seems to be a useful tool for the scrutiny of mood disorders in Portuguese patients with MS. The questionnaire is also sensitive to disease when compared to people with other severe illnesses, and with people without the disease. Keywords: multiple sclerosis, depression, anxiety, HADS